2021
DOI: 10.1177/0143034320975846
|View full text |Cite
|
Sign up to set email alerts
|

Ideal standards for policy on student self-harm: What research and practice tells us

Abstract: School communities face challenges in responding effectively to the rising incidence of student self-harm. Evidence-informed guidelines may provide a platform for schools to provide better responses and improve the outcomes of students who engage in self-harm. This paper critically reviews policies published in English targeted for schools or education settings on effective early identification and intervention for children and adolescent self-harm. A grey literature search was conducted using Start Page web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In order to appropriately and compassionately support children who self-harm, further trauma informed psychological education and training regarding identifying and responding to self-harm may be necessary for all staff, so teachers can provide students with adequate support, especially when school psychologists are not available (Simm et al, 2010;Townsend, Gray, et al, 2018;Townsend, Hasleton, et al, 2018). Guidelines have recently been published that provide guidance to schools to support effective responses to students who engage in self-harm (Matthews et al, 2021). Previous research has also suggested that pre-career training for teachers in responding to self-harm would be beneficial (Best, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In order to appropriately and compassionately support children who self-harm, further trauma informed psychological education and training regarding identifying and responding to self-harm may be necessary for all staff, so teachers can provide students with adequate support, especially when school psychologists are not available (Simm et al, 2010;Townsend, Gray, et al, 2018;Townsend, Hasleton, et al, 2018). Guidelines have recently been published that provide guidance to schools to support effective responses to students who engage in self-harm (Matthews et al, 2021). Previous research has also suggested that pre-career training for teachers in responding to self-harm would be beneficial (Best, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Self-harm is a significant public health concern [ 1 , 2 ], with suicide now recognized as the fourth-largest cause of death among 15–19-year-olds worldwide [ 3 , 4 ]. These issues are of serious concern in Australia also [ 5 ], with recent data from the Australian Institute of Health and Welfare (AIHW) reporting that death by suicide among people aged 18–24 years increased by 52% from 10.8 deaths per 100,000 in 2010 to 16.4 deaths in 2020 [ 6 ]. In addition, self-harm and suicide have emerged in recent years as the leading cause of disease burden in Australia among young people aged 15–25 [ 7 ], resulting in the Prime Minister of Australia declaring self-harm and suicide prevention among young persons to be a national priority [ 8 ].…”
Section: Introductionmentioning
confidence: 99%